Bohr effect of avian hemoglobins: Quantitative analyses based on the Wyman equation. (7th December 2016) - Okonjo, Kehinde O.
Abstract: The Bohr effect data for bar-headed goose, greylag goose and pheasant hemoglobins can be fitted with the Wyman equation for the Bohr effect, but under one proviso: that the pKa of His146β does not change following the T→R quaternary transition. This assumption is based on the x-ray structure of bar-headed goose hemoglobin, which shows that the salt-bridge formed between His146β and Asp94β in human deoxyhemoglobin is not formed in goose deoxyhemoglobin. When the Bohr data for chicken hemoglobin were fitted by making the same assumption, the pKa of the NH 3 + terminal group of Val1α decreased from 7.76 to 6.48 following the T→R transition. When the data were fitted without making any assumption, the pKa of the NH 3 + terminal group increased from 7.57 to 7.77 following the T→R transition. We demonstrate that avian hemoglobin Bohr data are readily fitted with the Wyman equation because avian hemoglobins lack His77β. From curve-fitting to Bohr data we estimate the pKa s of the NH 3 + terminal group of Val1α in the R and T states to be 6.33±0.1 and 7.22±0.1, respectively. We provide evidence indicating that these pKa s are more accurate than estimates from kinetic studies. Graphical abstract: Highlights: The Wyman equation does not fit most mammalian hemoglobin Bohr effect data. Dog hemoglobin, like avian hemoglobins, does not have His77β. The Wyman equation fits dog hemoglobin Bohr effect data. The Wyman equation fits avian hemoglobin Bohr effect data. pKa s of NH 3 + terminal group of Val1α: 6.48 in the R and 7.76 in T quaternary structure.